The Experience of Indonesian Migrant Workers in Taiwan during Covid-19 Pandemic: A ‘right-based’ Analysis - Gusman, Yuherina (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2021)
Covid-19, which has attacked the world since the end of 2019, has had a global impact both economically and socially to the world community. Taiwan is one of country categorized as quite successful in dealing with Covid-19. From December 2019 until March 2021 there were 177,578 reported cases in Taiwan with a total of 976 positive cases and resulted in 10 deaths. A very small number compared to other cases that occur in other parts of the world. However, behind all that successful story, migrant workers in Taiwan are still forgotten during the pandemics. Migrant workers, particularly Indonesian migrant workers, who make up the majority in Taiwan, receive the least sympathy and understanding from the community. Several human rights issues confronted Indonesia Migrant Workers during the Covid-19 pandemic, including discrimination, loss of spatial public space, strict mobility limitations, concern for the family in Indonesia, a higher burden of common mental health, and a lower quality of life than local society, difficulty accessing health services and masks, and difficulty returning home. The purpose of this paper is to demonstrate how Indonesian migrant workers' rights were violated in Taiwan during the two phases of the Covid-19 pandemic. The data was collected through interviews, observation, and then was analyzed using the "rights-based" approach. The first phase lasted from December 2019 to March 2020, when the pandemic was still in its early stages, and the second phase lasted from March 2020 to January 2021, after the Taiwan government succeeded in controlling the pandemic